Qualitative study of acceptability, benefits, and feasibility of a food-based intervention among participants and stakeholders of the RATIONS trial. - Sunita Sheel Bandewar; Madhavi Bhargava; Hema Pisal; Sharanya Sreekumar; Anant Bhan; Ajay Meher; Anurag Bhargava (PLOS Global Public Health)
A qualitative study was conducted during the RATIONS trial to explore the perceptions, experiences, and expectations of participants and stakeholders on the acceptability, benefits, and feasibility of the nutritional intervention to complement the trial findings for deeper exploration into why and how of these findings and other allied themes. Using purposive sampling, we recruited 58 individuals for 22 in-depth interviews (IDI) and four focus group discussions (FGDs) between January and June 2022. These included 12 patients with TB, six household contacts, and other stakeholders (18 trial members, 18 government community workers, and four National TB Elimination Program (NTEP) staff). All IDIs and FGDs were audio-recorded, transcribed, and translated. The codes were generated using an inductive process and categorized manually into themes, with direct quotes describing the themes. The intervention was found to be acceptable in terms of cultural compatibility, quality, quantity, and duration; considered beneficial in helping tolerate the adverse effects of medications, weight gain, and resuming work; and was considered life-saving by many during the COVID-19 pandemic. Other observations included food-sharing in the control arm, inability to regain pre-disease functional status despite weight gain, and preference for in-kind support. Community health workers expressed confidence in its feasibility and willingness to take responsibility for its implementation. The NTEP staff considered it feasible if necessary resources were provided. This qualitative inquiry reflected the perspectives and lived experiences of households experiencing poverty, food insecurity, TB and the stakeholders serving them. Their voices are relevant in framing policy and practice in the NTEP and future research in India and similar low-resource settings. The food-based intervention was perceived as acceptable, feasible, and beneficial for the recipients and the NTEP. Opinion on cash or support in kind was divided; many preferred in-kind support over cash, but others expressed a requirement for both.